Effects of genetically modified soybean on physiological variables and gut microbiota of Sprague-Dawley rats. - Elham Ashrafi-Dehkordi; Abdolvahab Alborzi; Gholamreza Pouladfar; Seyed Amin Abbasian; Seyed Mohammad Mazloomi (PLoS ONE)
Soybean is an important source of food and feed. To keep weeds out of soybean it is often genetically modified. The goal of the current study was to evaluate the effects of a diet containing 70% GM soybean on Sprague-Dawley rats. Two groups of rats were fed GM and non-GM soybeans for a period of 120 days, and their body weight, hematology and serum biochemistry were compared. In addition, the effect of the consumption of GM soybean on identified intestinal microbiota and antibiotic resistance was compared with the effect of the consumption of non-GM soybean. Total bacteria and six types of bacteria shared by humans and rats were detected by q-PCR. The results showed that the consumption of GM soybean did not result in any significant changes in body weight, hematology and serum biochemistry. The results of q-PCR indicated that compared with the consumption of non-GM soybeans, the consumption of GM soybean did not have a comparable effect on the abundance of total bacteria, namely Bifidobacterium group, Clostridium perfringens subgroup, Escherichia coli, Lactobacillus group, and the Bacteroides-Prevotella group. The results of antibiogram showed that the consumption of GM soybean did not change the resistance of E.coli, although it changed the resistance of E. faecalis against erythromycin (the GM group was significantly less resistant than non-GM group). Overall, the study indicated that the consumption of GM soybean did not exhibit adverse effects on physiological variables and gut microbiota of rats. However, the obtained antibiogram results indicated that it is necessary to further investigate the antibiotic resistance of the gut microbiota when GM food is consumed.